ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Yang Terdaftar Pada Indeks LQ-45 Periode 2011-2014) - Arifianto, Muhammad; Chabachib, Mochammad (Faculty of Economics and Business Diponegoro University, 2016)
Firm value is a depiction of how success is a firm in running their business. Therefore, this research is conducted to analyze the effect given by some factors such as Profitability (ROE), Leverage (DAR), and Firm Size (Size), and Price Earning Ratio (PER) to Firm Value (PBV) on the company that registered in the LQ-45 index between 2011-2014 period.The sample in this research are 22 companies that always exists on the LQ-45 index between 2011-2014 period.Â The sampling method used is purposive sampling. The data in this research obtained from the companiesâ€™ annual report. Data analysis in this research done with multiple linear regression method.The result from this research showed that Profitability, Firm Size, andÂ Price Earning Ratio have positive significant effect to Firm Value; while Leverage has a negative significant effect to Firm Value. The adjusted R2 score of 0,907 showed that ROE, DAR, Size, and PER have 90,7% to PBV, while the other 9,3% are determined by another variable.